An experimental and numerical study of evaporation reduction in a salt-gradient solar pond using floating discs. (15th January 2017) - Silva, Cristóbal; González, Daniel; Suárez, Francisco
Highlights: Evaporation reduction experiments in a salt-gradient solar pond. Evaporation suppression effect on the water and energy balance of a solar pond. Evaporation reduction improves the heat storage capacity of the pond. Reducing evaporation in solar ponds improve its economic benefits. Abstract: Salt-gradient solar ponds are water bodies that act as solar collectors with integrated storage that are a promising renewable energy source for low-temperature applications. Evaporation is an important challenge for efficient operation of solar ponds, especially in arid locations without water sources to replenish the evaporative losses. In this work, transparent partial covers were used to investigate how evaporation suppression affects both the water and energy balance of a laboratory-scale solar pond. In our experiments, the evaporation reduction efficiency was related to the cube root of the relative covered area. This evaporation reduction efficiency is smaller than that of natural water bodies because of the influence of the warm lower convective zone. Also, as the covered fraction of the surface area increased, the thickness of the non-convective zone decreased and the heat losses through this zone increased. As a result, the temperature in the lower convective zone did not increase as the covered fraction increased. Nonetheless, the heat content within the solar pond slightly increased, demonstrating that the reduction of evaporation improves the heat storage capacity of the pond. Moreover, an economic analysis showed that although the evaporation reduction efficiency in solar ponds is smaller than that of natural water bodies or reservoirs, the benefits related to the additional energy collected in the solar pond when reducing evaporation overcome the smaller water saving benefits. Therefore, suppressing evaporation in solar ponds not only is valuable in locations with no water to replenish the evaporative losses but also improves its economic benefits.